Dynamic Responses of Supported Beams with Intermediate Supports Under Moving Loads - Biaobiao Zhang; Steve Shepard (Shock and Vibration)
In this paper, a new beam shape function configuration method for determining transient responses of a finite Euler-Bernoulli beam with two intermediate supports excited by moving pressure wave loads is developed. To clarify this method, this beam structure is excited by the moving sinusoidal loads as an example. Transient responses of this beam structure are investigated and verified by the traditional finite element method. This method can be used to solve transient response problems of moving pressure loads exciting the beam structure with intermediate support. Actually it can be extended to solve other complicated beam structure problems.